Mewujudkan Kepastian Hukum Program Penjaminan Polis untuk Melindungi Pemegang Polis Asuransi (SETARA : Jurnal Ilmu Hukum, 2022)
The insurance industry shocked by cases of insolvency and corruption at PT Asuransi Jiwasraya (Persero) in 2018. Cases of insolvency and governance violations also occurred at certain insurance companies. The Financial Services Authority will impose sanctions on insolvent insurance companies, including written warnings, revocation of business licenses, and bankruptcy. The purpose of this study is to examine how legal certainty in a policy guarantee program can provide legal protection for policyholders when insurance companies face insolvency, liquidation, and bankruptcy. This study uses normative legal research with a descriptive and qualitative character. The focus of the research is positive law related to the application of legal certainty to the protection of insurance policyholders' rights. The results show that the Countermeasures taken by the Financial Services Authority do not yet provide adequate legal certainty for policyholders, so a policy guarantee program needs to be realized immediately as mandated by Article 53 of Law Number 40 of 2014 concerning Insurance.